FULL GENOME SEQUENCES OF CANINE DISTEMPER VIRUS STRAINS ISOLATED IN KAZAKHSTAN - Zholdybayeva , Elena; Momynaliev , Kuvat; Tarlykov , Pavel; Ramanculov , Erlan; Sandybayev , Nurlan; Orynbayev , Mukhit; Mamadaliyev , Seidigapbar (Eurasian Journal of Applied Biotechnology, 2013)
Periodic discoveries of dead Caspian seals on the Caspian seashore served as a basis for this study. Various carnivorous animals, basically dogs, foxes and ferrets, are susceptible to canine distemper virus. However, the range of hosts, susceptible to the virus has become wider over the past 20 years. Highly contagious viral disease of carnivores (Carré’s disease) is characterized by fever, acute catarrhal inflammation of the mucosa, skin rash, pneumonia, and severe damage to the nervous system. Fatality rate can reach 80-90%. Two canine distemper virus (CDV) strains, namely, Shuskiy strain and Phoca/Caspian/2007 strain have been sequenced and analyzed. DNA sequencing was performed according to Sanger method. Primers were designed using Primer Express 2.0. programme. Morphological properties of isolates were studied with electron microscopy. Cytopathic effect was studied in Vero cell culture. Both strains were isolated from different hosts within a 9 year time period. The first strain was isolated from a mink in 1998 and the second one was isolated from a seal in 2007. A comparison of the nucleotide sequences of both CDV strains has revealed their complete identity. Phylogenetic analysis of whole genome sequences of local strains with other strains from Genbank has showed that local strains form one cluster with Chinese strain, isolated form mink. A phylogenetic analysis of hemagglutinin gene of 79 CDV strains has indicated that both CDV strains belong to the group of vaccine type that is genetically distinct from the Asian and European genotypes.